PENINGKATAN HASIL BELAJAR BAHASA INDONESIA DENGAN MODEL DIRECTED READING THINKING ACTIVITY BERBANTU MEDIA AUDIO VISUAL PADA MATERI MENENTUKAN GAGASAN POKOK DALAM PARAGRAF BACAAN SISWA KELAS IV SDS GKPS BANGUN TOBING T.A 2023/2024 - Diaman Setiawan Barus; Leni Mailinda; Nuri Ramadhan (Pragmatik: Jurnal Ilmiah Ilmu Pendidikan, 2024)
This type of research is classroom action research, which consists of 4 stages, namely planning, implementing, observing and reflecting. Based on the results of the study, it can be concluded that through the application of the directed reading thinking activity model and audio-visual media it can improve student learning outcomes, namely the increase in the average pre-cycle (67.5%) 7 students (43.75%) who completed, cycle I ( 72.5%) as many as 9 students (56.25%) who completed and in cycle II (81.87%) as many as 13 students (81.25%) who completed and at the end who completed in cycle III (88.43%) ) as many as 14 students (87.5%). This proves that the directed reading thinking activity model and audio-viual media can improve learning outcomes in Indonesian for Class IV Students at SDS GKPS Bangun Tobing, Stm Hilir District, Deli Serdang Regency.